The influence of self-efficacy on the learning outcomes of critical thinking skills and understanding of concepts in a school-based management course - Albertus Hartana; I Nyoman Sudana Degeng; Dedi Kuswandi; Saida Ulfa; Elizabeth Mayasari (Jurnal Ilmu Pendidikan, 2024)
This study investigates the impacts of self-efficacy on self-regulated learning, critical thinking, and the outcomes of comprehending School-Based Management lectures. Additionally, it explores the influence of self-regulated learning on critical thinking and learning outcomes. To test the hypotheses, the SmartPLS 3 analytic method was employed. Findings indicate a significant positive effect of self-regulated learning on learning outcomes, establishing self-efficacy as a crucial factor for enhancing learning strategies and self-monitoring capabilities. The research confirms the beneficial effect of self-efficacy on critical thinking, highlighting its role in fostering key student competencies such as creativity, independence, and scientific inquiry. Furthermore, while self-regulated learning positively impacts critical thinking, self-efficacy was not found to directly affect learning outcomes. The study underscores the importance of self-regulated learning in advancing critical thinking skills, contributing valuable insights into the dynamics between self-efficacy, self-regulated learning, and educational achievement.